21ST CENTURY CHARACTER EDUCATION IN EARLY CHILDREN IN IMPLEMENTING ISLAMIC RELIGIOUS VALUES INTEGRATION OF LOCAL WISDOM IN PAUD PLUS PURI KENCANA SAMARINDA - Qamariah, Sa’da; Zamroni, Zamroni; Tamam, Badrut; Solekhin, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research explores local wisdom and the cultivation of Islamic religious values (PAI) in 21st century Character Education at PAUD Plus Puri Kencana, Samarinda. This research reveals the integration of the method of singing the Indun g-indung song, which is a regional song from East Kalimantan and contains Aqidah and moral values with 21st century character learning and the Unggah-ungguh method from Javanese tradition, to form noble morals in young children. The basis of this research is the finding that singing activities can increase children's interest and understanding in recognizing religious and moral values, and that the Javanese traditional Unggah-ungguh method can be integrated with Islamic moral values. The method used in this research is descriptive qualitative with class teachers as purposive respondents. Data was collected through interview surveys and documentation. The research results showed that the Indung-indung singing activity and the Unggah-ungguh method succeeded in integrating cultural and religious values in early childhood Islamic learning, as well as supporting the formation of 21st century character in early childhood. This research recommends the development of integrated learning models, teaching materials and innovative learning media to support 21st century character education and instill Islamic religious values through singing and Unggah-ungguh learning methods. Additionally, further research is needed to explore the long-term impact of these activities on child development